Audit Committees and Board of Directors on Financial Performance: The Moderating Role of Women on Boards in Indonesia - Intan Nibras Fahar; Farah Margaretha Leon; Purba, Yosephina E (Universitas Trisakti, 2025)
This study aims to analyze the effect of Audit Committee Size, Women on the Audit Committee, Audit Committee Activity, Board Meetings, Board Independence, and Board Financial Expertise on Financial Performance, with Women on Boards as a moderating variable, and Firm Size and Firm Age as control variables. Financial performance in this study focused on return on assets and equity. The data used in this study is secondary data from the financial statements and annual reports of non-financial companies listed on the Indonesia Stock Exchange during the period 2019-2023. The research sample was selected using a purposive sampling method, resulting in 50 companies being sampled. Analysis of the data used to test the hypothesis is multiple regression analysis using the Eviews 10 program. The results of this study indicate that the variables of Audit Committee Activity and Firm Age have a significant positive effect on financial performance. Meanwhile, the variables of Audit Committee Size, Woman on Audit Committee, Board Meeting, and Board Financial Expertise have a significant negative effect on financial performance. Furthermore, Woman on Boards is proven to moderate the relationship between audit committee characteristics and financial performance. This study implies that management should consider the bigger Firm Age and Audit Committee Size as factors that can enhance financial performance. A larger Audit Committee Size, Woman on the Audit Committee, Board Meeting, and Board Financial Expertise may reduce financial performance.